2020
DOI: 10.1098/rsos.191596
|View full text |Cite
|
Sign up to set email alerts
|

Compressor performance modelling method based on support vector machine nonlinear regression algorithm

Abstract: To overcome the difficulty of having only part of compressor characteristic maps including on-design operating point, and accurately calculate compressor thermodynamic performance under variable working conditions, this paper proposes a novel compressor performance modelling method based on support vector machine nonlinear regression algorithm. It is compared with the other three neural network algorithms (i.e. back propagation (BP), radial basis function (RBF) and Elman neural networks) from the perspective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In this paper, the remaining 3124 knowledge data samples are used for test this scenario. And three common neural networks of GRNN, BP and RBF from another our previous work [36] are used as comparative machine learning models, the relative errors by these methods are shown in figures 11 to 15 and the root mean square errors by these methods are shown in Table 6. 6 and form figures 11 to 15, we can see that, compared with other machine learning models, the proposed deep learning model shows best diagnostic accuracy, and the overall root mean square error by the deep learning model does not exceed 0.033%, and the maximum relative error by the deep learning model does not exceed 0.36%, which illustrates the proposed method has great application potential.…”
Section: Sfmentioning
confidence: 99%
“…In this paper, the remaining 3124 knowledge data samples are used for test this scenario. And three common neural networks of GRNN, BP and RBF from another our previous work [36] are used as comparative machine learning models, the relative errors by these methods are shown in figures 11 to 15 and the root mean square errors by these methods are shown in Table 6. 6 and form figures 11 to 15, we can see that, compared with other machine learning models, the proposed deep learning model shows best diagnostic accuracy, and the overall root mean square error by the deep learning model does not exceed 0.033%, and the maximum relative error by the deep learning model does not exceed 0.36%, which illustrates the proposed method has great application potential.…”
Section: Sfmentioning
confidence: 99%
“…The introduction of the kernel function achieves the purpose of increasing the dimension, and the added parameters are adjustable and optimizable to prevent overfitting questions. Many scholars have indicated that the radial basis function net is an efficient tool for the fitting of a nonlinear relationship [25,33]. Therefore, in this study, a radial basis function was selected as the SVR kernel function to discover and interpret the nonlinear relationship between the stripping peak currents of Pb 2+ and Cu 2+ and the Pb 2+ concentration.…”
Section: Svr Modelingmentioning
confidence: 99%
“…A large number of ML methods for regression problems have been proposed and used in diverse engineering applications [6]- [8], [16], [17] to name some of them. Nevertheless, we focus on existing work that compares different approaches to regression problems for engineering applications.…”
Section: Related Workmentioning
confidence: 99%